AI in Education: Transforming Student Engagement for the Digital Age - Baskara Qazuaini Karim; Haryanto Haryanto; Eny Yulia Susanti (Jurnal Penelitian Pendidikan IPA, 2025)
This research explores the transformative role of Artificial Intelligence (AI) in enhancing student engagement in higher education, specifically focusing on Educational Technology students at Yogyakarta State University, Indonesia. Through a descriptive quantitative approach, the study investigates how AI integration affects learning motivation, implementation patterns, and overall educational experiences in the digital era. A purposive sample of 25 fourth-semester students completed a structured questionnaire to assess their knowledge, usage patterns, and perceptions of AI in learning. Results revealed a high level of AI awareness (96%) and experience (100%) among students, though only 64% reported regular implementation in academic activities. Student perceptions were overwhelmingly positive, with 96% acknowledging AI's effective impact on learning, 92% reporting significant learning support, and 88% expressing intention to continue using AI in future studies. Despite these positive outcomes, the motivational aspect of AI received a comparatively lower rating (68%), suggesting areas for improvement. The study identifies AI's potential to create personalized, adaptive, and interactive learning environments while addressing concerns about over-reliance and ethical considerations. This research contributes to understanding how AI can be optimally integrated into higher education to enhance student engagement while maintaining fundamental educational values. The findings suggest that AI serves not as a replacement for educators but as a powerful complementary tool that transforms the educational landscape in the digital age.